2015
DOI: 10.1021/acschembio.5b00651
|View full text |Cite
|
Sign up to set email alerts
|

The Supersized Class III Lanthipeptide Stackepeptin Displays Motif Multiplication in the Core Peptide

Abstract: Lanthipeptides are ribosomally synthesized and post-translationally modified peptides bearing the characteristic amino acids lanthionine and/or labionin. Here, we report on the discovery and characterization of the stackepeptins, produced by the Actinomycete Stackebrandtia nassauensis DSM-44728(T). The stackepeptins are the first supersized class III lanthipeptides to be discovered. Unlike other class III lanthipeptides, they consist of three lanthionine/labionin moieties instead of two. In this study, both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 30 publications
4
47
0
2
Order By: Relevance
“…130 The in vitro reconstitution of LabKC demonstrated another unusual feature, the requirement of guanosine triphosphate (GTP) or deoxy-GTP for dehydration instead of ATP that is utilized by class II LanM enzymes. 477 Subsequent studies on a series of LanKC enzymes showed that the nucleotide specificity is not uniform: EryKC involved in erythreapeptin biosynthesis is ATP dependent, 132 AciKC that generates catenulipeptin accepts ATP, GTP, CTP, or TTP as a cosubstrate, 130 and StaKC 484 and CurKC 131 responsible for stackepeptin and curvopeptin biosynthesis, respectively, can utilize all NTPs/dNTPs but prefer purine nucleoside triphosphates as the phosphoryl donor for the central kinase domain (for structures of these class III lanthipeptides, see Figure 48). …”
Section: Class III and Iv Lanthipeptide Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…130 The in vitro reconstitution of LabKC demonstrated another unusual feature, the requirement of guanosine triphosphate (GTP) or deoxy-GTP for dehydration instead of ATP that is utilized by class II LanM enzymes. 477 Subsequent studies on a series of LanKC enzymes showed that the nucleotide specificity is not uniform: EryKC involved in erythreapeptin biosynthesis is ATP dependent, 132 AciKC that generates catenulipeptin accepts ATP, GTP, CTP, or TTP as a cosubstrate, 130 and StaKC 484 and CurKC 131 responsible for stackepeptin and curvopeptin biosynthesis, respectively, can utilize all NTPs/dNTPs but prefer purine nucleoside triphosphates as the phosphoryl donor for the central kinase domain (for structures of these class III lanthipeptides, see Figure 48). …”
Section: Class III and Iv Lanthipeptide Biosynthesismentioning
confidence: 99%
“…Phylogenetic analysis of class III enzymes that make Lan or Lab did not provide any clear indications that could be predictive of the outcome. 36 Even more interestingly, some LanKC enzymes such as EryKC 132 and StaKC 484 can form both Lan and Lab in the same product (e.g., Figure 48 for the product of EryKC). Although the molecular mechanism of how the enzymes achieve the remarkable tandem cross-linking reaction resulting in labionin is still mostly unclear, several insightful observations have been reported.…”
Section: Class III and Iv Lanthipeptide Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome mining for lanthipeptides has been fruitful, leading to the discovery of bicereucin [27], the cerecidins [28], and stackepeptin [29], among others. An interesting BGC was discovered in Ruminococcus flavefaciens FD-1, a commensal bacterium occurring in the rumen of animals, that encoded two putative class II lanthipeptide synthetases and twelve putative lanthipeptide precursor peptides.…”
Section: Examples Of Bottom-up Ripp Discoverymentioning
confidence: 99%
“…Obwohl frühere Studien nahelegen, dass LP von Klasse‐I Lanthipeptiden eine helikale Struktur annehmen, zeigen neueste Co‐Kristallisationen der Dehydratase NisB (Nisin) mit dem Vorläuferpeptid NisA, dass das LP vielmehr eine β‐Strang‐Konformation einnimmt, mit der es an einem dreisträngigen antiparallelen β‐Faltblatt in NisB bindet . Für Klasse‐III Lanthipeptide wird ein konserviertes, N‐terminales LLDLQ‐Motiv im LP von Stackepeptin und verwandten Lanthipeptiden vorgeschlagen . Müller et al.…”
Section: Introductionunclassified